An update on current management strategies for antiphospholipid syndrome-related thrombosis. (February 2014) - Rossi, Andrea; Colorio, Cecilia; Puente, Dolores; Forastiero, Ricardo
The antiphospholipid syndrome (APS) is an autoimmune disorder characterized by clinical symptoms of venous or arterial thrombosis, and/or pregnancy morbidity in the presence of autoimmune antiphospholipid antibodies (aPL). Primary thrombosis prevention with daily low-dose of aspirin is not indicated in asymptomatic persistently aPL persons. However, aspirin may be useful for some individuals with autoimmune diseases or with multiple aPL positivity. Secondary prevention of recurrent thrombosis is commonly made using vitamin K antagonists. A moderate intensity of anticoagulation is recommended in the majority of APS patients and the duration of treatment is usually indefinite. In cases with the catastrophic APS, an aggressive therapy is highly recommended using immunosuppression and anticoagulants. This article will also review significant advances in new therapeutic strategies for the management of APS-related clinical events.